Antibiotic residues in poultry and food safety risks in North Cotabato, Philippines - AYESHA B. HADJI IBRAHIM; CROMWEL M. JUMAO-AS; ANNIELYN D. TAMPUS; SHARON ROSE M. TABUGO; LIZA A. ADAMAT; MARK ANTHONY I. JOSE; MARIA ELENA N. TANABE; OLIVE A. AMPARADO (Smujo International, 2025)
Abstract. Hadji Ibrahim AB, Jumao-As CM, Tampus AD, Tabugo SRM, Adamat LA, Jose MAI, Tanabe MEN, Amparado OA. 2025. Antibiotic residues in poultry and food safety risks in North Cotabato, Philippines. Asian J Agric 9: 463-471. Poultry production in North Cotabato, Philippines, remains a key agricultural sector, yet the extent of antimicrobial residue contamination in retail chicken meat is poorly documented. This study aimed to detect and quantify antibiotic residues in organic and non-organic chicken meat sold in public wet markets using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Thirty-six whole dressed chickens (18 organic and 18 non-organic) were purchased across six municipalities, yielding 72 tissue samples (wings and legs). Six antibiotics namely doxycycline, enrofloxacin, norfloxacin, tilmicosin, amoxicillin, and trimethoprim/sulfamethoxazole were targeted. Doxycycline was the most frequently detected compound, present in 100% of non-organic and 50% of organic samples. Fluoroquinolones (enrofloxacin/norfloxacin) and tilmicosin (macrolide) were detected exclusively in non-organic leg tissues at frequencies of 66.7% and 50%, respectively. Residue concentrations ranged from <1.5 ?g/kg to 37.2 ?g/kg, with all values below Maximum Residue Limits (MRLs). No samples contained amoxicillin or trimethoprim/sulfamethoxazole. While a two-way ANOVA revealed no significant differences in mean residue concentrations by chicken part or production type (p>0.05), Chi-square tests revealed significant differences in detection frequency by production type (p<0.001) and by municipality (p=0.029). Non-organic samples consistently exhibited higher detection rates, with Pikit and Pigkawayan identified as geographic hotspots. These findings expose gaps in residue withdrawal compliance, certification credibility, and traceability in informal retail markets. The detection of residues in uncertified “organic” chicken underscores the urgent need for strengthened organic certification enforcement, farmer education, and municipality-level surveillance to align with the Philippine AMR Action Plan and ASEAN regional goals.